2016
DOI: 10.1089/cmb.2016.0052
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Direct Evolutionary Selection for Strong Folding and Mutational Robustness Within HIV Coding Regions

Abstract: A large number of studies demonstrated the importance of different HIV RNA structural elements at all stages of the viral life cycle. Nevertheless, the significance of many of these structures is unknown, and plausibly new regions containing RNA structure-mediated regulatory signals remain to be identified. An important characteristic of genomic regions carrying functionally significant secondary structures is their mutational robustness, that is, the extent to which a sequence remains constant in spite of des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…28 This model was initially introduced in the context of enumerative combinatorics and was used by us before for studying other viruses. 16,17 We used the original source code which can be found in http://csb.cs. mcgill.ca/sparcs (7 February 2017, date last accessed).…”
Section: Randomization Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…28 This model was initially introduced in the context of enumerative combinatorics and was used by us before for studying other viruses. 16,17 We used the original source code which can be found in http://csb.cs. mcgill.ca/sparcs (7 February 2017, date last accessed).…”
Section: Randomization Modelsmentioning
confidence: 99%
“…mRNA secondary structure is believed to be in the most stable conformation when minimum amount of free energy is exerted (the MFE obtains the most negative value). The local MFE-profiles were constructed by applying a 39 nt length sliding window to a genomic sequence: in each step the MFE of a local subsequence enclosed by the corresponding window was calculated by Vienna (v. 2.1.9) package RNAfold 31 function with default parameters (see, also 16,32 ). This function predicts the MFE and the associated secondary structure for the input RNA sequence using a dynamic programming based on the thermodynamic nearest-neighbor approach (the Zucker algorithm).…”
Section: Folding Energy Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…and concluded that various “hidden” regulatory signals are encoded in the viral genome which naturally affect their evolution and replication rate. Codes analogous to the viral “hidden” codes may have appeared in the molecules prior to the origin of cellular life [35,36,37,38]. …”
Section: Viral and Replicator Connectionsmentioning
confidence: 99%